The effect of AA5083H116 2-layer MIG welding speed on physical and mechanical properties - M Mudjijana; Viktor Malau; Urip Agus Salim (Journal of Material Processing and Characterization, 2020)
Metal welding can be performed on 1 layer or more depending on the thickness of the plate welded. In the case of 3-mm-thick plates, high-efficiency welding can be carried out on 1 layer if appropriate welding speed, voltage, and amperage are applied. If two layers are to be used, sound weld of 3-mm-thick plates can be achieved if higher welding speed and lower voltage and amperage are applied. This research was intended to conduct 2-layer MIG weld works at welding speeds of ≥10, 13, and 16 mm/s in accordance with previous research studies and to analyze the physical and mechanical properties generated. This research employed the AA5083H116 material, ER5356 electrode, and argon gas. During the welding processes, the thermal cycles were recorded, and after the processes, the welding results were observed for the macro- and microstructures and for the optimal welding speed under an SEM. In addition, tensile tests, Vickers microhardness tests, and corrosion tests were also undertaken. The results show that the 2-layer MIG welding at the welding speed of 10 mm/s produced the best physical and mechanical properties.